2020
DOI: 10.3389/fphar.2020.00231
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Retinol-Binding Protein 4 as a Possible Biomarker of Treatment Response for Ankylosing Spondylitis: An Array-Based Comparative Study

Abstract: Objective: To explore proteins associated with ankylosing spondylitis (AS) and to investigate potential proteins that may predict treatment response of adalimumab (ADA) in AS patients. Methods: In the discovery cohort, 39 AS patients and 20 healthy controls (HCs) were included, and 16 AS patients received ADA treatment for 24 weeks after included. In the validation cohort, 43 AS patients and 39 HCs were enrolled, and all 43 patients received ADA treatment after enrollment. Blood samples and clinical informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Previous studies have evaluated the value of cytokine levels in predicting the response of axSpA patients to TNF inhibitors 19,21–24 . For instance, one study showed that CRP and Jun N‐terminal kinase pathway‐associated phosphatase (JKAP) might predict the treatment response to TNF inhibitors 21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have evaluated the value of cytokine levels in predicting the response of axSpA patients to TNF inhibitors 19,21–24 . For instance, one study showed that CRP and Jun N‐terminal kinase pathway‐associated phosphatase (JKAP) might predict the treatment response to TNF inhibitors 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated the value of cytokine levels in predicting the response of axSpA patients to TNF inhibitors. 19,[21][22][23][24] For instance, one study showed that CRP and Jun N-terminal kinase pathway-associated phosphatase (JKAP) might predict the treatment response to TNF inhibitors. 21 Another study exhibited that circulating baseline IL-6 and erythrocyte sedimentation rate might reflect the response to adalimumab in AS patients.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of RBP4 have been associated with inflammation in metabolic disorders like insulin resistance [9,13], metabolic syndrome [14,15], fatty liver [16], cardiovascular diseases like atherosclerosis [17], and chronic inflammatory diseases such as psoriasis [8]. Moreover, altered levels of RBP4 have been reported in patients with rheumatic diseases, including rheumatoid arthritis (RA) [18,19] and ankylosing spondylitis [20]. RBP4 was also specifically related to RA co-morbidities in RA patients [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the pathogenesis of bone erosion and bone formation in AS is not completely understood 5 . In recent years, many studies have reported that cytokines play a vital role in disease pathology, 6‐9 and other studies have reported that the dysregulation of the immune system and bone metabolism may play a critical role in AS etiology 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…However, the pathogenesis of bone erosion and bone formation in AS is not completely understood. 5 In recent years, many studies have reported that cytokines play a vital role in disease pathology, [6][7][8][9] and other studies have reported that the dysregulation of the immune system and bone metabolism may play a critical role in AS etiology. 10,11 Leukemia inhibitor factor (LIF), also known as differentiationstimulating factor and differentiation-inducing factor, is a member of the interleukin (IL)-6 family, which is widely expressed in multiple types of tissue and is a pleiotropic cytokine.…”
Section: Introductionmentioning
confidence: 99%